Periconceptional Maternal Mediterranean Diet Is Associated With Favorable Offspring Behaviors and Altered CpG Methylation of Imprinted Genes - House, John S.; Mendez, Michelle; Maguire, Rachel L.; Gonzalez-Nahm, Sarah; Huang, Zhiqing; Daniels, Julie; Murphy, Susan K.; Fuemmeler, Bernard F.; Wright, Fred A.; Hoyo, Cathrine (Frontiers in Cell and Developmental Biology, 2018)
Background: Maternal diet during pregnancy has been shown to influence the child neuro-developmental outcomes. Studies examining effects of dietary patterns on offspring behavior are sparse. Objective: Determine if maternal adherence to a Mediterranean diet is associated with child behavioral outcomes assessed early in life, and to evaluate the role of differentially methylated regions (DMRs) regulating genomically imprinted genes in these associations. Methods: Among 325 mother/infant pairs, we used regression models to evaluate the association between tertiles of maternal periconceptional Mediterranean diet adherence (MDA) scores derived from a Food Frequency Questionnaire, and social and emotional scores derived from the Infant Toddler Social and Emotional Assessment (ITSEA) questionnaire in the second year of life. Methylation of nine genomically imprinted genes was measured to determine if MDA was associated with CpG methylation. Results: Child depression was significantly associated with maternal MDA (Bonferroni-corrected p = 0.048). While controlling for false-discovery, compared to offspring of women with the lowest MDA tertile, those with MDA scores in middle and high MDA tertiles had decreased odds for atypical behaviors (OR (95%CI) = 0.40 (0.20, 0.78) for middle and 0.40 (0.17, 0.92) for highest tertile)), for maladaptive behaviors (0.37 (0.18, 0.72) for middle tertile and 0.42 (0.18, 0.95) for highest tertile) and for an index of autism spectrum disorder behaviors (0.46 (0.23, 0.90) for middle and 0.35 (0.15, 0.80) for highest tertile). Offspring of women with the highest MDA tertile were less likely to exhibit depressive (OR=0.28 (0.12, 0.64)) and anxiety (0.42 (0.18, 0.97)) behaviors and increased odds of social relatedness (2.31 (1.04, 5.19)) behaviors when compared to low MDA mothers. Some associations varied by sex. Perinatal MDA score was associated with methylation differences for imprinted control regions of PEG10/SGCE (females: Beta (95%CI) = 1.66 (0.52, 2.80) - Bonferroni-corrected p = 0.048; males: -0.56 (-1.13, -0.00)), as well as both MEG3 and IGF2 in males (0.97 (0.00, 1.94)) and -0.92 (-1.65, -0.19) respectively. Conclusions: In this ethnically diverse cohort, maternal adherence to a Mediterranean diet in early pregnancy was associated with favorable neurobehavioral outcomes in early childhood and with sex-dependent methylation differences of MEG3, IGF2, and SGCE/PEG10 DMRs.